A dispersão da memória e da escrita em Milton Hatoum e Lobo Antunes - Azevedo, Vera Lucia Ramos de (2011)
The purpose of this work is to investigate the course of memory and writing in two contemporary novels: Relato de um certo Oriente, by Milton Hatoum, and Não entres tão depressa nessa noite escura, by António Lobo Antunes, taking into consideration the questionable place the enterprise of memory, as wel as the enterprise of writing, reachs in the mentioned works. For this reason, the analysis intends to follow the way memory is put in action by the narrators, since both of them elect family history as a place of absortion of other memory places, as history and forgetfulness, what can reveal the restricted or obstructed course followed by memory to recuperate past time. Ruins, mourning and melancholy, besides displacement, cision and disturbance of identity that affect narrators constitute the scenery of memory in both novels. This scenery may be enlarged through the relation between texts, that takes place in both novels, able to reveal the work of citation that is employed as a memory of writing , signaled by the novels as dispersion. This dispersed memory, that results also into a dispersed writing, is expressed by the discontinued movement of narrative, perceived through the dissemination of narrators, in Hatoum, or through the upset of narrative caused by invention/imagination, in Antunes